Differentiated Learning Approach for Improving Report Text Learning Outcomes for Tenth Graders - Yossi Stefani; Rudi Anton Simanjuntak; Ismail Petrus (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
The use of differentiated learning approaches to learning has become a trend in the MERDEKA Curriculum. This study aimed to improve English learning outcomes of report text through the differentiated learning approach based on students' readiness. This study utilized Classroom Action Research conducted in class XB at SMAN 4 Palembang with 34 students. Data for this research were obtained from tests, observations, tasks, and documentation. The data were analyzed qualitatively and quantitatively. Qualitative analysis involved data processing, reading, classifying, and interpreting, while quantitative data were analyzed using percentage analysis. This study consisted of two cycles, starting with the pre-cycle. Initially, 12 students (35.3%) passed, while 22 students (64.7%) did not reach the Minimum Learning Mastery Standard (KKM) with an average score of 63.82. After Cycle I, the number of students who successfully completed the tasks increased to 15 (44.1%), with 19 students (55.9%) not reaching the target, and the average score improved to 71.17. In Cycle II, a significant improvement was observed, with 33 students (97%) reaching the KKM, and only 1 student (3%) did not pass, resulting in an average score of 89.11. The differentiated learning approach effectively enhances English learning outcomes. Teachers should employ differentiated learning for enhanced results and create engaging classrooms.